Instrumental Assessment of Scots Pine Trees (Pinus Sylvestris L.) - Ivan A. Garus, Elena M. Runova,; Savchenkova, Vera A.; Mukhacheva, Anastasiya N. (Opción, 2019)
The article presents the results of a study of the quality of stem wood of mature and overripe Scots pine trees (Pinus sylvestris L.) using the methods of non-destructive testing of wood with the help of ultrasonic tomography unit Arbotom® and Resistograph 4450. As a result, the integrated use of Arbotom® and Resistograph 4450 devices is necessary in order to obtain a more objective assessment of the state of tree stands and individual trees. As a conclusion, the density of wood at the root crown and at a height of 150 centimeters varies in different trees.